James Cone's Constructive Vision of Sin and the Black Lives Matter Movement - Miller, Liam (2020)
The Black Lives Matter movement faces persistent opposition by those who shift the discussion from structural and societal inequality toward individual responsibility. This socio-political outworking of a universalised and individualised doctrine of sin is common amongst White, conservative Christian communities. James H. Cone's constructive doctrine of sin is an alternative in the contemporary context. For Cone, sin is particularly expressed based on the concrete existence of a community, and its overcoming is bound up in the oppressed's struggle for liberation and the affirmation of their humanity. This paper explores Cone's community conception of sin, demonstrating its power to combat the idol of Whiteness and equip churches to take practical steps to ensure that Black lives matter in a White society.
Keywords: Black Lives Matter; James Cone; Whiteness; Ethics; Liberation; Sin